2020
DOI: 10.1098/rsos.200482
|View full text |Cite
|
Sign up to set email alerts
|

A ratiometric fluorescent probe for pH detection based on Ag 2 S quantum dots–carbon dots nanohybrids

Abstract: In this study, a novel ratiometric fluorescent nanoprobe for pH monitoring has been developed by synthesizing red fluorescent Ag 2 S quantum dots (Ag 2 S QDs) and green fluorescent carbon dots (CDs) nanohybrids (Ag 2 S CDs) in one pot using CDs as templates. The nanoprobe exhibits dual-emission peaks at 500 and 670 nm under a single-excitation wavelength of 450 nm. The red fluorescence can be selectively quenched by increasing pH, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The gas sensor prepared by CDs–WO 3 has excellent cycling stability and anti-interference ability. Lei et al 122 constructed a proportional fluorescent nanoprobe for pH detection (Fig. 9c).…”
Section: Applicationsmentioning
confidence: 99%
“…The gas sensor prepared by CDs–WO 3 has excellent cycling stability and anti-interference ability. Lei et al 122 constructed a proportional fluorescent nanoprobe for pH detection (Fig. 9c).…”
Section: Applicationsmentioning
confidence: 99%
“…It can also be seen from the CIE chromaticity diagram that the emission region of CD-oPD remained in the green region (Figure 4D). Therefore, from these results, it was shown that individual CDs are unable to monitor wound healing efficiently, due to the difficult detection of color and/or fluorescence variations (Song et al, 2017;Lei et al, 2020;Xu et al, 2020;Li et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In light of the limitations of single-channel nanoparticles, researchers are developing ratiometric sensors to improve the sensitivity of CDs to pH. (Song et al, 2017;Lei et al, 2020;Xu et al, 2020;Li et al, 2021;Silva et al, 2022). Ratiometric fluorescent sensors typically exhibit dual emission bands at different wavelengths (Silva et al, 2022).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum dots (QDs) belong to the family of semiconductor nanocrystals, which are widely used as emerging fluorescent probes. 8 QDs have the advantages of a broad absorption spectrum, size-dependent emission, high quantum yield and high optical stability. [9][10][11] The main disadvantages of traditional QDs with CdSe as the core are their high biotoxicity, low biocompatibility and a complex synthetic pathway.…”
Section: Introductionmentioning
confidence: 99%